Цукровий діабет 2-го типу як чинник, що обтяжує перебіг інфаркту міокарда у хворих з артеріальною гіпертензією - Шатохіна, І. В. (Clinical Endocrinology and Endocrine Surgery, 2012)
The article describes a comparative assessment of myocardial infarction course in patients with diabetes mellitus and without disturbances of carbohydrate metabolism depending on the presence or absence of hypertension history.